2009
DOI: 10.1590/s1413-70542009000400008
|View full text |Cite
|
Sign up to set email alerts
|

Eficiência relacionada à absorção e utilização de nitrogênio, fósforo e enxofre, em plantas de cafeeiros enxertadas, cultivadas em vasos

Abstract: O estudo da eficiência nutricional de plantas de cafeeiro (Coffea. arabica) enxertadas visou conhecer preliminarmente os potenciais de clones de Conilon (C. canephora) como porta-enxertos quanto à absorção e utilização de N, P e S. O experimento foi realizado no viveiro do setor de cafeicultura do Departamento de Fitopatologia da Universidade Federal de Viçosa, utilizando vasos de 20 litros em ambiente aberto. Foram empregados como porta-enxerto cinco progênies famílias de meio-irmãos de clones elites de C. ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…The liming associated to the fertilization provided the supply of P to the evaluated plants due to the increase of the pH of the soils (Table 3), making it more available in the solution of the soils facilitating the absorption of the same by the plants (Opala, 2017;Cunha et al, 2018a, b). The absorption of this nutrient, according to Tomaz et al (2009), depends on the morphological and physiological characteristics of the roots, however, their importance in the absorption process depends on the root access to the nutrient. When there is no limitation on the arrival of the ion at the root surface, the physiological factors are more important than the morphological ones regarding nutrient absorption (Delhaize et al, 2007;Balemi & Negisho, 2012).…”
Section: Efficiency In Nutrient and Al Absorption Transport Use Andmentioning
confidence: 99%
See 1 more Smart Citation
“…The liming associated to the fertilization provided the supply of P to the evaluated plants due to the increase of the pH of the soils (Table 3), making it more available in the solution of the soils facilitating the absorption of the same by the plants (Opala, 2017;Cunha et al, 2018a, b). The absorption of this nutrient, according to Tomaz et al (2009), depends on the morphological and physiological characteristics of the roots, however, their importance in the absorption process depends on the root access to the nutrient. When there is no limitation on the arrival of the ion at the root surface, the physiological factors are more important than the morphological ones regarding nutrient absorption (Delhaize et al, 2007;Balemi & Negisho, 2012).…”
Section: Efficiency In Nutrient and Al Absorption Transport Use Andmentioning
confidence: 99%
“…between shoot nutrient content (NC sh ) and root dry weight (RDW), demonstrating plant's ability to extract nutrients from the soil, which differs among species (Swiader et al, 1994;Fageria & Moreira, 2011;Sathiyavani et al, 2017). Some species have an extensive root system while others have high uptake per unit of root length, that is, a high nutrient uptake rate (Tomaz et al, 2009). Transport efficiency (TE) is defined as the relation between total shoot nutrient content (TNC SH ) and total plant nutrient content (TNC P ) multiplied by 100 (Li et al, 1991) and indicates the plant's ability to transport nutrients from the root to the shoot.…”
Section: Introductionmentioning
confidence: 99%
“…As observed for macronutrients (Tomaz et al, 2004;Tomaz et al, 2008;Tomaz et al, 2009), the nutritional efficiency of coffee plants to B, Zn, Cu and Mn shows variation with the combination graft and rootstock used. Combining Catuaí Vermelho IAC-15 and rootstocks ES-26 and ES-23 benefited the efficiency of use of B and Zn (Tomaz et al, 2011).…”
Section: Systematic Analysis Of the Nutritional Efficiency Of Coffea mentioning
confidence: 86%
“…It was observed that MG 6851 Oeiras and H 419-10-3-1-5 had no benefit by grafting, showing high efficiency in nutrient utilization (Tomaz et al, 2004). The efficiency of absorption and utilization of N, P and S has been studied in plants of C. arabica grafted on C. canephora (Tomaz et al, 2009) and evaluated at 18 months of age. It was concluded that the use efficiency of N, P and S (Tomaz et al, 2009) and K, Ca and Mg (Tomaz et al, 2008) varied depending on the combination of rootstock and graft as already evidenced (Tomaz et al, 2004).…”
Section: Systematic Analysis Of the Nutritional Efficiency Of Coffea mentioning
confidence: 99%
See 1 more Smart Citation